The behavioural consequences of reduced sea water pH in decapod crustaceans ... - De La Haye, Kate (University of Plymouth, 2012)
The studies presented in this thesis were designed to investigate the effects of reduced sea water pH on the behaviour of intertidal decapod crustaceans, both within the context of the variations occurring naturally in the pH of rock pool habitats, and in relation to predicted changes to ocean pH resulting from ocean acidification and potential carbon dioxide (CO2) leaks from carbon capture storage (CCS) sites. Recent studies on marine fish have shown behavioural disruptions as a result of increased CO2 concentrations in sea water and reduced pH, but the effects on crustaceans are as yet unknown. The first two studies investigated the effects of reduced pH upon the olfactory behaviour of the prawn Palaemon elegans and the hermit crab Pagurus bernhardus, focussing on their responses to food odours. Short-term (five day) exposures to highly reduced pH (pHNBS = 6.60, 6.80) revealed disruptions to the chemo-sensory behaviour of both species with a reduction in their ‘sniffing’ response, and the inability of P. ...